2023
DOI: 10.1021/acs.jpcc.3c03514
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Interfacial Thermal Conductance on the Thermoplasmonic Response of Metal/Polymer Hybrid Nanoparticles under Nanosecond Pulsed Illumination

Javier González-Colsa,
Fernando Bresme,
Pablo Albella

Abstract: Janus nanoparticles containing plasmonic materials have attracted great attention in the thermoplasmonic community due to their potential for applications in thermoelectronics or biomedicine. A significant number of thermoplasmonic applications rely on the heating of nanostructures by using pulsed excitation lasers. The heating generated in these nanostructures is often transferred to other regions via material−fluid interfaces. This heat transfer dynamics is controlled by the interfacial thermal conductance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…González-Colsa et al has shown a temperature gap of 10 K with a gold/polymer semi-shell nanostructure under pulsed heating, though the temperature gap under steady-state conditions with the semi-shell remains unclear. 36 Drawing parallels with the first type of JNP investigated in our study, we speculate a significantly enhanced directional heating potential for this type of JNP under ultra-fast pulsed heating compared to continuous heating, attributable to similar factors such as thermal confinement. We anticipate that ultra-fast pulsed heating could be an effective method for harnessing directional heating across various types of JNPs.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…González-Colsa et al has shown a temperature gap of 10 K with a gold/polymer semi-shell nanostructure under pulsed heating, though the temperature gap under steady-state conditions with the semi-shell remains unclear. 36 Drawing parallels with the first type of JNP investigated in our study, we speculate a significantly enhanced directional heating potential for this type of JNP under ultra-fast pulsed heating compared to continuous heating, attributable to similar factors such as thermal confinement. We anticipate that ultra-fast pulsed heating could be an effective method for harnessing directional heating across various types of JNPs.…”
Section: Discussionsupporting
confidence: 75%
“…34 These asymmetries have been harnessed to regulate the thermal transport around the JNP and lead to directional heating. [34][35][36][37] Directional heating with the rst type of JNPs has enabled novel applications with JNPs, such as thermophoretic nanomotors, 33,35,38 nano tweezers, 39,40 Janus nano pen injection, 41 and energy management. 42 For the second type of JPNs, recent theoretical studies have shown the possibility of directional heating with signicantly smaller (∼5 nm) than the rst type JNPs (50-200 nm), 34 thus promising to open the new size range for potential applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation